2015
DOI: 10.1016/j.jaging.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Gendered emotion work around physical health problems in mid- and later-life marriages

Abstract: The provision and receipt of emotion work—defined as intentional activities done to promote another’s emotional well-being—are central dimensions of marriage. However, emotion work in response to physical health problems is a largely unexplored, yet likely important, aspect of the marital experience. We analyze dyadic in-depth interviews with husbands and wives in 21 mid-to later-life couples to examine the ways that health-impaired people and their spouses provide, interpret, and explain emotion work. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
102
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 39 publications
9
102
1
7
Order By: Relevance
“…Researchers have found that women in both same-sex and different-sex relationships do more emotion work than men to allow and encourage the sharing of personal thoughts, feelings, and emotions between relational partners (Umberson, Thomeer, & Lodge, 2015). When men do engage in emotion work, they describe it in masculinized terms, similar to how they would describe themselves as financial providers (Thomeer, Reczek, & Umberson, 2015). In Thomeer et al’s (2015) sample of heterosexual couples in which one partner had significant health problems, men explained doing emotion work because they were “being a rock” for their wives (p. 16).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Researchers have found that women in both same-sex and different-sex relationships do more emotion work than men to allow and encourage the sharing of personal thoughts, feelings, and emotions between relational partners (Umberson, Thomeer, & Lodge, 2015). When men do engage in emotion work, they describe it in masculinized terms, similar to how they would describe themselves as financial providers (Thomeer, Reczek, & Umberson, 2015). In Thomeer et al’s (2015) sample of heterosexual couples in which one partner had significant health problems, men explained doing emotion work because they were “being a rock” for their wives (p. 16).…”
Section: Introductionmentioning
confidence: 95%
“…When men do engage in emotion work, they describe it in masculinized terms, similar to how they would describe themselves as financial providers (Thomeer, Reczek, & Umberson, 2015). In Thomeer et al’s (2015) sample of heterosexual couples in which one partner had significant health problems, men explained doing emotion work because they were “being a rock” for their wives (p. 16). Still, the men in the sample did not report doing nearly as much emotion work as their wives, even when their wives were the ones with health problems.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It also supports theories about ''feminization'' of older men, at least in partner care (Pérez Díaz 2003). Caregiving may affect how (older) men negotiate their social roles and their masculinity (Calasanti 2010;Ribeiro et al 2007;Thomeer et al 2015;Wallroth 2016). Some critics find it unfair that male caregivers get more attention and question whether their caregiving is really similar to that of women (Milne & Hatzidimitriadou 2003).…”
Section: Discussionmentioning
confidence: 99%